Urban policy and the exterior city : Federal, State, and corporate impacts upon major cities - Savitch, H. V. (Pergamon policy studies on urban affairs., 1979)
Urban Policy and the Exterior City: Federal, State and Corporate Impacts upon Major Cities emphasizes the idea that problems that riddle cities are not matters of local choice, but are rooted in the larger environment of American society. This book is divided into three main topics- the dynamic of the exterior city, exterior cities in the arena of national government, and exterior cities in the arena of middle government. In these topics, this publication specifically discusses the emergence of the exterior city; political economy and policy; reinforcing and meliorist prototypes; and meliorist.